"These Labourers in the Field of Public Work": Librarians, Discrimination and the Meaning of Equal Pay. (November 2019) - Kirkby, Diane; Jordan, Caroline
Abstract : Librarianship has long been recognised as a numerically female-dominated occupation. Despite demonstrating a standard pattern of a sex-segregated labour force, it has suffered neglect in historical studies of women's work. This article positions Australia's librarians in the history of white-collar public service workers, and librarianship as illustrative of important themes of twentieth-century women's labour history. For smart, educated, ambitious women, librarianship offered professional standing, economic security and opportunity for advancement. Strategies of overt discrimination, however, deliberately kept women librarians out of senior administrative positions and confined them to the lower-paying jobs. Librarians in state and municipal libraries worked under public service regulations that established a dual labour market of wages and conditions for clerical and professional workers. Key decisions between 1918 and 1922 explicitly advantaged men in recruitment, wages and promotion, denying women similar opportunities. Studying the history of women librarians sheds new light on the meaning of professional workers' struggle for equal pay.